1975
DOI: 10.1002/cncr.2820360937
|View full text |Cite
|
Sign up to set email alerts
|

“Skip” metastases in osteosarcoma

Abstract: Careful study of 40 cases of osteosarcoma without evidence of multifocal disease, pulmonary metastasis, or history of exposure to predisposing factors has given histologic evidence of microscopic foci of osteosarcoma separate from the primary focus of osteogenic sarcoma. These "skip" lesions are to all pathologic examination completely separate from the primary focus of osteogenic sarcoma. They are more often found proximal to the primary, both intraosseously and transarticularly. Histologically, these "skips"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

1978
1978
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(25 citation statements)
references
References 27 publications
1
21
0
2
Order By: Relevance
“…8,10,18) Metastasis via the vertebral venous plexus system may be a plausible mechanism of bone-to-bone metastasis without evidence of pulmonary metastasis. 7,9,15) Multifocal osteosarcoma can be classified according to histology, patient age, and time at presentation of multiple osseous lesions. 2) Type I patients are less than 18 years of age, with multiple histologically anaplastic osseous lesions appearing within 5 months of the initial presentation.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,18) Metastasis via the vertebral venous plexus system may be a plausible mechanism of bone-to-bone metastasis without evidence of pulmonary metastasis. 7,9,15) Multifocal osteosarcoma can be classified according to histology, patient age, and time at presentation of multiple osseous lesions. 2) Type I patients are less than 18 years of age, with multiple histologically anaplastic osseous lesions appearing within 5 months of the initial presentation.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Skip metastazlar, Enneking ve Kagan tarafından aynı kemikte, primer lezyondan anatomik olarak ayrılan, eş zamanlı, daha küçük tümör odakları veya eklemin diğer tarafında eşzamanlı daha küçük tümör odağı olarak tanımlanır. [10,11] Sistemik evreleme, akciğer ve kemik metastazları için bilgisayarlı tomografi (BT) ve radyonüklid kemik görüntülemeyi içermelidir (3).…”
Section: Genel Bilgilerunclassified
“…6). Enneking reported that it occurred in 20% of osteosarcoma cases, but it is actually not so common [10] . It is seen in highgrade lesions.…”
Section: Metastases (M Factor)mentioning
confidence: 99%